2022
DOI: 10.1101/2022.06.20.496788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retinal metabolism: Evidence for uncoupling of glycolysis and oxidative phosphorylation via Cori-, Cahill-, and mini-Krebs-cycle

Abstract: The retina consumes massive amounts of energy, yet its metabolism remains poorly understood. Here, we manipulated retinal energy metabolism under entirely controlled conditions and utilised 1H-NMR metabolomics, in situ enzyme detection, and cell viability readouts to uncover the pathways of retinal energy production. Our experiments resulted in varying degrees of photoreceptor degeneration, while the inner retina and retinal pigment epithelium were essentially unaffected. Notably, rod photoreceptors relied str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…Thus, MCs could convert lactate into pyruvate through LDH-B to fuel mitochondria and produce ATP through oxidative phosphorylation. However, MCs lack the enzymes pyruvate kinase M2 (PKM2) and lactate dehydrogenase A (LDH-A) required for lactate production (Chen et al, 2022;Chinchore et al, 2017;Lindsay et al, 2014;Rajala et al, 2018). It is possible that the expression of pyruvate kinase M1 (PKM1) and LDH-B are sufficient to sustain lactate synthesis in MCs and release it through MCT1 and MCT4 when metabolically required.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MCs could convert lactate into pyruvate through LDH-B to fuel mitochondria and produce ATP through oxidative phosphorylation. However, MCs lack the enzymes pyruvate kinase M2 (PKM2) and lactate dehydrogenase A (LDH-A) required for lactate production (Chen et al, 2022;Chinchore et al, 2017;Lindsay et al, 2014;Rajala et al, 2018). It is possible that the expression of pyruvate kinase M1 (PKM1) and LDH-B are sufficient to sustain lactate synthesis in MCs and release it through MCT1 and MCT4 when metabolically required.…”
Section: Introductionmentioning
confidence: 99%
“…1b, c). Notably, under all conditions, the number of TUNEL-positive cells in the ONL was much higher: SR = 19.9 ± 6.9%, n = 6, p < 0.0001, AR-C = 16.6 ± 5.2%, n = 6, p = 0.0007, Shikonin = 14.5 ± 5.9%, n = 6, p = 0.0018, reflecting the sensitivity of photoreceptors to metabolic disruptions 6 .…”
Section: Inhibition Of Lactate Transport Increases Cell Death In the ...mentioning
confidence: 89%
“…However, a demonstration of this transporter´s function and its role in inner retinal physiology was missing. In vascular retinas, inner retinal cells can obtain metabolites from alternative sources 5 , and previous studies have demonstrated the ability of the neuroretina to be metabolically flexible to meet its energy demands 6 . Although that study focused on the outer retina, some important enzymes involved in different metabolic pathways were expressed in the INL, supporting a similar metabolic flexibility for the inner retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation